Self-medication of sleeping pills among MBBS students in a medical college of West Bengal, India - Dalui, Saikat Kumar; Datta, Angana; Ghosh, Aritra; Biswas, Suvadip; Roy, Uttam Kumar; Biswas, Supreeti (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Psychological stress, anxiety, depression and sleep disturbance are highly prevalent in medical students and therefore they are at higher risk of using sleeping pills defined as any pharmaceutical preparation inducing sleep. There is currently paucity in data describing the prevalence of sleeping pill use among medical students in India. Objective: To evaluate the prevalence of sleeping pill use among medical students in Burdwan Medical College (BMC). Methods: A cross sectional study was done by anonymous questionnaires from MBBS students enrolled at BMC. Questionnaire consisted of social and demographic variable and use of sleeping pills, tobacco and alcohol since enrollment. Collected data were analyzed by Athen's insomnia scale and DASS-21. Results: With response rate72.2% (397 out of 550) and of 397 respondants (1st yr-97+2nd yr-90+3rd yr part I-114+3rd yr part II-96), 6.3% reported use of sleeping pill at some time since enrollment. Athen's insomnia scales showed 27% poor sleepers. According to DASS-21, 44% respondents were depressive, 61.96% anxious, and 31.73% stressed. Insomnia were found to significantly (p value <0.0001) associated with sleeping pill use. Majority (96%) of sleeping pill uses were self-medicated. Conclusions: Tendency to use sleeping pill is very less (majority self-medicated), though a substantial proportion of medical undergraduate students were found to be depressed, anxious, stressed revealing a neglected area of students' psychology requiring urgent attention.